Analisis praktik manajemen rantai pasokan pada UMKM - Rosita Fitriyani; Yuli Liestyana; Agung Satmoko (Universitas Kristen Maranatha, 2022)
This study analyzes micro, small and medium enterprises (MSMEs) implementing supply chain management (SCM) practices between suppliers, manufacturers, distributors, and customers to encourage supply chain performance and good firm performance. This data collection was obtained from interviews and questionnaires conducted in parallel. The sampling technique used is purposive sampling, with 50 MSMEs – determination of the samples based on considering MSMEs that have implemented SCM practices. The analytical tool used is a path analysis model. The variables used in this study are aspects of SCM practices: customer relationship management, supplier relationship management, goal congruence, and information sharing. The results show that the dimensions of SCM practices partially positively influence firm performance and supply chain performance. Unfortunately, supply chain performance cannot mediate SCM practices on MSMEs performance. The supplier relationship management variable is considered to have the lowest value among other variables. Suggestions of this research that MSMEs can make are expected to work together with suppliers to improve product quality, such as evaluating product raw materials from suppliers, as well as routinely making continuous product improvements to maintain product quality owned by MSMEs.